Skin self-examination and long-term melanoma survival. Issue 4 (August 2016) - Paddock, Lisa E.; Lu, Shou En; Bandera, Elisa V.; Rhoads, George G.; Fine, Judith; Paine, Susan; Barnhill, Raymond; Berwick, Marianne
Abstract : To evaluate the effect of skin self-examination (SSE) on melanoma mortality, we estimated the survival for individuals performing SSE compared with those who did not. Participants were from a previously carried out case–control study, who were newly diagnosed melanoma cases in 1987–1989. A 20-year survival analysis was carried out using death (event) and other causes of death (competing). Cumulative incidence functions were evaluated using Gray's test and proportional subdistribution hazards regression models were fitted to study the effect of SSE and other covariates on melanoma survival. Forty-five percent of patients died, with 48.4% melanoma deaths. Individuals who did not perform SSE experienced a continuous increase in the risk of melanoma death trending toward significance for nearly 20 years after diagnosis, whereas melanoma deaths in skin self-examiners plateaued before 10 years after diagnosis ( P =0.32). Univariate analyses suggested a 25% lower risk of melanoma death for those who performed SSE [hazard ratio (HR)=0.75, 95% confidence interval (CI)=0.43–1.32, P =0.32]. After adjusting for competing risks, the multivariate risk estimate was above one (HR=1.12, 95% CI=0.61–2.06, P =0.71). Skin awareness (HR=0.46, 95% CI=0.28–0.75, P ⩽0.01) was associated independently with a decreased risk of melanoma death. Although we did not find a significant association between melanoma mortality and SSE when adjusting for competing mortality and other covariates, we extended previous findings that increased skin awareness and tumor thickness are strongly inversely related to survival. Research is needed to continue developing best practices for melanoma screening and to further explore the components of SSE and long-term melanoma survival.